Soil Rather Than Xylem Vulnerability Controls Stomatal Response to Drought - Carminati, Andrea; Javaux, Mathieu (Trends in plant science, 2020)
The current trend towards linking stomata regulation to plant hydraulics emphasizes the role of xylem vulnerability. Using a soil–plant hydraulic model, we show that xylem vulnerability does not trigger stomatal closure in medium-wet to dry soils and we propose that soil hydraulic conductivity loss is the primary driver of stomatal closure. This finding has two key implications: transpiration response to drought cannot be derived from plant traits only and is related to soil–root hydraulics in a predictable way; roots and their interface with the soil, the rhizosphere, are key hydraulic regions that plants can alter to efficiently adapt to water limitations. We conclude that connecting below- and aboveground hydraulics is necessary to fully comprehend plant responses to drought. There is an increasing need for mechanistic and predictive models of transpiration and stomatal response to drought and soil water availability. It has been hypothesized that stomatal regulation is predictable based on plant and soil hydraulics.The current trend towards a greater consideration of plant hydraulics in earth system science emphasizes xylem vulnerability, neglecting the explicit role of soil and root hydraulics.The importance of root and soil hydraulic conductivity on plant water status is well accepted, but difficult to measure.There is increasing evidence that plants adapt the conductivity of their roots as well as that of the soil in their vicinity, the rhizosphere, to match the soil conditions and atmospheric water demand, contributing to the regulation of plant water status and transpiration.